Weighted weak type inequalities for modified Hardy operators and geometric means operators in dimensions one and greater. - Ortega-Salvador, Pedro; Ramírez Torreblanca, Consuelo (Elsevier, 2007)
We characterize the pairs of weights such that the geometric mean operator , defined for positive functions f on by verifies the weak type inequality in the case . Similar results are obtained for the n-dimensional geometric mean operator defined by
Política de acceso abierto tomada de: https://beta.sherpa.ac.uk/id/publication/11377
Keywords: Desigualdades (Matemáticas); Análisis matemático; Modified Hardy operators; Weighted weak type inequalities; Geometric means operators